Distribution of microplastics in surface water of tropical urban lakes: A case study in Ha Noi, Vietnam - Mai, Huong; Hoi Bui, Van; Duong Dao , Thanh; Duong Nguyen, Thanh; Thien Nguyen, Danh; Khanh Vu, Toan; Hoang Anh Chu, Nguyen; Quan Tran, Manh; Stragy, Emillie (Vietnam Journal of Earth Sciences, 2023)
Microplastics are nowadays considered ubiquitous pollutants since they have been found widespread in all environmental compartments, particularly in aquatic systems. In urban water bodies, municipal wastewater discharges and overflows of combined storm and wastewater drains are the sources of microplastic pollution. The investigation was performed on the distribution of microplastics in the surface water of three urban lakes: West Lake, Yen So Lake, and Bay Mau Lake, from February 2020 to January 2021. Results show that microplastics were widely and unevenly distributed in all three lakes in Ha Noi and reached a high abundance on the site of West Lake, which is most intensively surrounded by population density, restaurants/bars, and aquaculture activities. Microplastic abundance was highest in February 2020 for all three urban lakes, with 154.92 items m-3 in Bay Mau, 589.46 items m-3 in West Lake, and 139.86 items m-3 in Yen So Lake. There was a decreasing trend in the following sampling times of July, October 2020, and January 2021 (range: Bay Mau: 16.02-59.04 items m-3; West Lake: 36.51-201.08 items m-3; Yen So: 14.07-67.27 items m-3). The dominant microplastics in urban lakes were fibers with a size of 1-3 mm, while microplastic fragments were 0.045-0.3 mm2. Analysis of the chemical composition of microplastics indicated dominance by rayon (13.5-58.5%) and polyethylene terephthalate (14.1-30.8%). This study is an essential reference for understanding the characteristics of the variation in microplastics in urban lakes to reduce local microplastic pollution effectively.